Pengaruh Annealing Terhadap Tingkat Kestabilan Efisiensi Sel Surya p-i-n a-Si:H Doping Delta - Amiruddin Supu; Dilla M; Jasruddin Daud Malago; Fitri Suryani Arsyad; Toto Winata; M. Barmawi (Indonesian Journal of Physics, 2001)
Hydrogenated amorphous silicon (a-Si:H) solar cells with δ-doped p-layer have been fabricated using double chamber Plasma Enhanced Chemical Vapor Deposition (PECVD). 10 % Silane (SiH4), diborane (B2H6) and phosphine (PH3) gases in hydrogen (H2) gas were used as gas sources. δ-Doped p-layer was deposited by using very thin boron layer as dopant source. Current (I) - voltage (V) characteristic measurement was done using xenon lamp as light source with power of 250 watts and voltage of 24 volts. The result shows that the efficiency of δ-doped p-i-n a-Si:H solar cell without annealing decreases from 5.39 % to 3.49 % as the illumination time increases from 0 hours to 2.5 hours. The stable efficiency obtained is3.6 %. It means that there is an efficiency drop of 33.15 %. Solar cell efficiency annealed at temperature of 150OC decreases from 8.59 % to 6.69 % as the illumination time increases from 0 hours to 2.5 hours. Its stable efficiency obtained is 7.11 %. It means that there is an efficiency drop of 17.23 %. Thus the annealing process decreases the efficiency drop.